2021
DOI: 10.21203/rs.3.rs-399454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Inclusion of Under-Served Groups in Trials Methodology Research: An Example from Ethnic Minority Populations’ Views on Deferred Consent

Abstract: Background: Deferred consent is used to recruit patients in emergency research, when informed consent cannot be obtained prior to enrolment. This model of consent allows studies to recruit larger numbers of participants, especially where a surrogate-decision maker may be unavailable to provide consent. Whilst deferred consent offers the potential to promote trial diversity by including under-served groups, it is ethically complex and views about its use amongst these populations requires further exploration. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…An animation aimed at adults enrolled in emergency care research which describes RWPC was developed by another research team (CoMMiTED Study) [108]. Systematic reviews have explored stakeholders' views about the acceptability of RWPC [109], including ethnic minority populations' views [110]. Such studies have found that RWPC is generally acceptable to patients, families, and practitioners but highlighted the importance of contextual factors.…”
Section: Current Research and Guidancementioning
confidence: 99%
“…An animation aimed at adults enrolled in emergency care research which describes RWPC was developed by another research team (CoMMiTED Study) [108]. Systematic reviews have explored stakeholders' views about the acceptability of RWPC [109], including ethnic minority populations' views [110]. Such studies have found that RWPC is generally acceptable to patients, families, and practitioners but highlighted the importance of contextual factors.…”
Section: Current Research and Guidancementioning
confidence: 99%